2019
DOI: 10.1016/j.cis.2019.101995
|View full text |Cite
|
Sign up to set email alerts
|

Surface nanobubbles: Theory, simulation, and experiment. A review

Abstract: Surface nanobubbles (NBs) are stable gaseous phases in liquids that form at the interface with solid substrates. They have been particularly intriguing for their high stability that contradicts theoretical expectations and their potential relevance for many technological applications. Here, we present the current state of the art in this research area by discussing and contrasting main results obtained from theory, simulation and experiment, and presenting their limitations.We also provide future perspectives … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
33
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 56 publications
(36 citation statements)
references
References 160 publications
(362 reference statements)
2
33
0
1
Order By: Relevance
“…[8][9][10][11][12][13][14][15] A similar debate which lasted for many years took place after surface nanobubbles emerged and became the focus of attention about two decades ago. 16 The present situation is exacerbated by the lack of a full rational explanation of the mechanism behind the long-term stability of BNBs. 6,[17][18][19] A number of speculative interpretations have been postulated but a complete physical model has yet to emerge.…”
Section: Introductionmentioning
confidence: 99%
“…[8][9][10][11][12][13][14][15] A similar debate which lasted for many years took place after surface nanobubbles emerged and became the focus of attention about two decades ago. 16 The present situation is exacerbated by the lack of a full rational explanation of the mechanism behind the long-term stability of BNBs. 6,[17][18][19] A number of speculative interpretations have been postulated but a complete physical model has yet to emerge.…”
Section: Introductionmentioning
confidence: 99%
“…Some researchers have summarized and reviewed different stability theories or models of bulk and surface nanobubbles in recent years [2] , [5] , [6] . However, there is no effective research on the stability mechanisms of bulk and surface nanobubbles in an acoustic field.…”
Section: Proposed Generation and Stability Mechanisms Of Nanobubbles In Acoustic Fieldsmentioning
confidence: 99%
“…Nanobubbles include bulk and surface nanobubbles. Surface nanobubbles are described as spherical caps that are a few nanometers to tens of nanometers high and about 1 μm wide [5] , [6] . They are well studied in the literature and proven to be gas filled entities [7] , [8] , although the origin of their stability is still in dispute [9] , [10] , [11] , [12] , [13] , [14] , [15] .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In particular, using a model disjoining pressure, Svetovoy et al (2016) recently showed that surface-interface interactions significantly affect the shapes and contact angles of nanobubbles. Recent reviews by Theodorakis & Che (2019), Qian, Arends & Zhang (2019) and Lohse & Zhang (2015) discuss the latest experimental approaches, simulation studies and capillary models of surface nanodrops and nanobubbles. Interesting and promising fully microscopic approaches for computing the disjoining pressure of adsorbed liquid films were recently developed by MacDowell (2011), MacDowell et al (2014) and Nold et al (2014).…”
Section: Introductionmentioning
confidence: 99%